Chemical implementation of finite-state machines. - Hjelmfelt, A (1992)
With methods developed in a prior article on the chemical kinetic implementation of a McCulloch-Pitts neuron, connections among neurons, logic gates, and a clocking mechanism, we construct examples of clocked finite-state machines. These machines include a binary decoder, a binary adder, and a stack memory. An example of the operation of the binary adder is given, and the chemical concentrations corresponding to the state of each chemical neuron are followed in time. Using these methods, we can, in principle, construct a universal Turing machine, and these chemical networks inherit the halting problem